Effectiveness of assertive case management on repeat self-harm in patients admitted for suicide attempt: Findings from ACTION-J study - Furuno, Taku; Nakagawa, Makiko; Hino, Kosuke; Yamada, Tomoki; Kawashima, Yoshitaka; Matsuoka, Yutaka; Shirakawa, Osamu; Ishizuka, Naoki; Yonemoto, Naohiro; Kawanishi, Chiaki; Hirayasu, Yoshio (Journal of affective disorders, 2018)
Self-harm is an important risk factor for subsequent suicide and repetition of self-harm, and a common cause of emergency department presentations. However, there still remains limited evidence on intervention in emergency department settings for individuals who self-harm. This multicentre, randomised controlled trial was conducted at 17 general hospitals in Japan. In total, 914 adult patients admitted to emergency departments for a suicide attempt and had a DSM-IV-TR axis I disorder were randomly assigned to two groups, to receive either assertive case management (intervention) or enhanced usual care (control). Assertive case management was introduced by the case manager during emergency department admissions for suicide attempts, and continued after discharge. Interventions were provided until the end of the study period (for at least 18 months and up to 5 years). The number of overall self-harm episodes per person-year was significantly lower in the intervention group (adjusted incidence risk ratio (IRR) 0.88, 95%CI 0.80–0.96, p=0.0031). Subgroup analysis showed a greater reduction of overall self-harm episodes among patients with no previous suicide attempt at baseline (adjusted IRR 0.73, 95% CI 0.53–0.98, p=0.037). Patients younger than 20 years and patients who self-harmed but were not admitted to an emergency department were excluded. The present study showed that assertive case management following emergency admission for a suicide attempt reduced the incident rate of repeat overall self-harm. •The assertive case management reduced the incident rate of repeat overall self-harm.•Reduction was greater among patients with no previous suicide attempt at baseline.•The intervention group had fairly good adherence to the assertive case management.